NURSING CLINICAL RECORDS: SETTING OF STANDARDS AT HOSPITAL DE CLÍNICAS-UFPR - Gisele Grespan Suarez; Leomar Albini; Maria Luiza Hexsel Segui; Maria Cristina Paganini (Universidade Federal do Paraná, 2000)
This paper presents a proposal for setting Nursing Clinical Records Standards (PAE) in the University Hospital of Parana, based on courses with nursing teams. Between April and May of 2000, a three-hour course was given on nursing clinical records to 826 nursing professionals, divided in 42 groups. The objective was to set a standard for nursing records based on reflections with the nursing team, presenting, discussing and approving a proposal to be adopted in all nursing services. Three other courses with the nurses from all the hospital units were promoted in June of the same year, so that those would be prepared to act as facilitators in the implementation process of this proposal. Currently, methods to follow and evaluate the proposal are under organization.